History of the Emergence of the Khawarij and Murji'ah - Elly Warnisyah Harahap; Jesika Pebiola; Mahdy Husnul Widad; Nadia Gita Sari; Roni Riski Hasibuan; Eka Agustina; Aldino Ilham (al-Afkar, Journal For Islamic Studies, 2025)
This research explores the historical emergence of the Khawarij and Murji’ah sects within early Islamic history, aiming to understand their origins, doctrinal differences, and impacts on Islamic thought. The study addresses the primary research question: how did the Khawarij and Murji’ah sects arise, and what were the key theological and political factors that influenced their development? Utilizing a historical-analytical method, this research examines primary sources, including early Islamic texts and historical records, as well as secondary scholarly analyses. The findings reveal that the Khawarij emerged as a radical faction following the Battle of Siffin, emphasizing strict piety and rejecting any form of sin among leaders, whereas the Murji’ah advocated a more lenient stance, deferring judgment of sinners to God. The study concludes that the Khawarij and Murji’ah significantly shaped early Islamic discourse on faith, leadership, and community, leaving a lasting legacy on Islamic jurisprudence and theology. This research highlights the complex interplay of theology and politics in the formation of early Islamic sects, providing deeper insights into the dynamics of religious movements.